Anterior Cruciate Ligament Tear Treated with Arthroscopic Primary Repair - A Case Report and Literature Review - Armughan Ahmar, Adnan Qamar, Saad Sultan Rana, Mian Abdullah Anwar, Rehan Raza Shan, Muhammad Haider Ali (Pakistan Journal of Medical & Health Sciences, 2024)
Anterior cruciate ligament (ACL) tear is one of the most common injuries encountered in Orthopaedics worldwide1. ACL is a vital ligament attached on the medial wall of the lateral femoral condyle, the lateral intercondylar ridge marking its anterior border, proximally. Distally, it attaches between the intercondylar eminences on the anterior tibia.It consists of two bundles, anteromedial and posterolateral. Primarily, it prevents the anterior translation of the tibia on the femur2. In the extended knee, the posterolateral bundle is tight and the anteromedial bundle is lax. As the knee is flexed, the anteromedial bundle tightens and the posterolateral bundle relaxes. The anteromedial bundle is the primary restraint against anterior tibial translation while the posterolateral bundle stabilizes the knee in full extension especially against rotatory loads. The nerve supply to the ACL originates from the tibial nerve serving as vasomotor, sensory and proprioceptive functions. The blood supply to the ACL originates from branches of the middle genicular artery which form a network around the ligament.